Pengembangan Video Pembelajaran Interaktif Berbasis Teknologi tentang Pembangkit Listrik Tenaga Uap (PLTU) Menggunakan Model ADDIE - Alwy Misbakhudin; Muhammad Akmal Raihan; Sahmawati Sahmawati; Jessen Parulian Sianturi; Muhammad Raihan Galih; Didik Aribowo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Steam Power Plant (SPP) material is considered a complex topic because it involves thermodynamic concepts and mechanical processes occurring within closed components, making it difficult for students to observe directly. This study aims to develop and evaluate the feasibility of interactive technology-based learning videos as supporting media in electrical engineering education. The research employed a Research and Development (R&D) method using the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation phases. The analysis phase identified students’ needs to visualize the water-steam cycle and understand the operational processes of steam power plants. During the design phase, storyboards and animation concepts for the main SPP components were created. The development phase produced interactive learning videos using Canva and CapCut, which were validated and deemed feasible by subject matter experts and media experts. The implementation stage demonstrated that the media could be effectively integrated into the learning process. Furthermore, the evaluation results revealed highly positive student responses, with an average score of 4.4 out of 5.0. Based on these findings, the developed interactive learning video is considered feasible, practical, and effective in enhancing students’ understanding of Steam Power Plant concepts.